PSYCHOLOGICAL OPERATIONS: FROM THE COMMUNICATION, MEDIA, PROPAGANDA, AND SOCIO-CULTURAL PERSPECTIVE - Hendra Kaprisma (The Republic of Indonesia Defense University, 2020)
This millennial era that is inseparable with technological advancement, the role of media and communication become more crucial. Those two components shape up and influence human psychological development. Media and communication are two aspects that intertwined from both good and bad influence. Those good and bad stigmas are also inseparable from propaganda. The strength of propaganda depends on whether or not the socio-cultural element is accurately used to deliver the selected message. Sciences regarding social system have become more important because it is related to potential target to support the psychological operations. The psychological operations consisted of delivering a particular message or information through selected media (product) to influence or modify the behavior of the receiver (target audience). In the context of national resilience, astagatra is also known as one of the aspects that influence the success of psychological operations. Therefore, this paper will discuss the study of psychological operations from several disciplines such as communication, media, propaganda, and socio-cultural perspective. The study regarding history and development of psychological operations will be explained using critical-literacy methods strengthened by literature review. This research finds that psychological operations are one of the ways that shown to influence human mindset and trait, or behavior to a specific target audience that supported by intertwining aspects such as communication, media, propaganda, and socio-cultural aspects that significant to the success of psychological operations of a particular country.